Growth, development and yield of safflower genotypes in response to environmental variations - Mosupiemang, Marang; Emongor, Vallantino E.; Malambane, Goitseone; Mapitse, Renameditswe (Journal of Phytology, 2023)
Safflower (Carthamus tinctorius L.) is a crop that is drought tolerant and grown in arid and semi-arid lands (ASALs) for its commercial utility as vegetable oil, animal feed, cut flower, leafy vegetable, pharmaceuticals, foods colorant, textile dye, cosmetics, and biofuel production. These important attributes make safflower an ideal crop to diversify the economy and improve the socioeconomic status of many smallholder farmers in ASALs. This study evaluated the growth, development, and yield of five safflower genotypes in three different locations in the southern part of Botswana under farmers’ fields during winter and summer. The results showed that there was a significant (P ≤ 0.05) genotypic variability for all phenological development (days to emergence, stem elongation, and flowering), plant growth (plant height and shoot biomass), the yield and yield components (number of branches/plant, number of capitula/plant and 1000-seed weight), oil content and oil yield. However, genotypes did not vary significantly (P ≥ 0.05) in number of primary branches/plant. The results showed that winter planting significantly (P ≤ 0.05) promoted safflower growth and yield than planting in summer. The growth, development, yield, and yield components of safflower genotypes varied across locations with Ramonaka being the most favorable. The GGE biplot revealed that genotype Kenya-9819 was found to be the most stable and adaptable with above-average yields. Sebele winter planting was the best representative environment and most suitable for discriminating genotype performance. The genotype by yield*trait combination (GYT) biplot revealed that genotypes ranked as Kenya9819 > Turkey > Sina > PI537636 > Gila. The results suggested that safflower was best planted in winter and that Kenya9819 was the best genotype to be planted in the greater Gaborone region.